Why Hydrological Maze: The Hydropedological Trigger? Review of Experiments at Chuzhou Hydrology Laboratory. Issue 1 (12th April 2018) - Gu, Wei-Zu; Liu, Jiu-Fu; Lin, Henry; Lin, Jin; Liu, Hong-Wei; Liao, Ai-Min; Wang, Niu; Wang, Wen-Zhon; Ma, Tao; Yang, Na; Li, Xue-Gang; Zhuo, Peng; et al.
Abstract : Core Ideas: Hydropedological factors are key to revealing the hydrological maze. Hydropedological factor plays the role of "creator" in runoff composition and runoff generation. Hydropedological factor plays the role of "originator" of hydrological heterogeneity. Hydropedological factor plays the role of "producer" of hydrological puzzles. Hydrology is an old discipline due to its early origination, as well as a young discipline due to its insufficient scientific foundation as a natural science. Thus hydrology has long been haunted by a debate between natural functionalities found in observations vs. model results built on many simplified assumptions. We define the hydrological maze as puzzles, paradoxes, or complexity involved in hydrologic measurements and interpretations. The objective of this study was to reveal the hydrological maze through a comprehensive review of decades of work since the 1980s on observations and experiments using a combination of natural and artificial catchments at the Chuzhou Hydrology Laboratory in China, highlighting the role of hydropedology in hillslope and catchment hydrology based on long‐term monitoring of surface and subsurface flows at various soil depths and at different spatial scales. A conception has emerged that indicates the fundamental control of hydropedological factors (such as soil types, soil properties, and their spatial variations) as the trigger for the hydrological maze, including runoff generation, runoff composition, flow heterogeneity, and various hydrological puzzles. It is clear that the vadose zone is the key source for nonlinear and dissipative complexity in the hydrological maze that is intertwined with hydrochemical and hydroecological dynamics. Therein lies the hope for new hydrological insights and possible solutions to the hydrological maze.